ANALISIS KELAYAKAN FINANSIAL USAHA PENANGKARAN BENIH BAWANG MERAH DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA (Financial Feasibility Analysis of Shallot Seeds Breedimg in South Tonsewer Village District of Tompaso Barat, Minahasa Regency) - Aditia Christiani Onibala; Caroline B.D. Pakasi; Eyverson Ruauw (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
Shallots are one of the horticultural crops that have high demand, so the government tried to meet the needs of the community by providing assistance in running a shallots breeding business in Minahasa Regency, which is located in Tonsewer. This research is only based on one informant, because the breeding place is managed only by him. The purpose of this study is to look at the development of this business through a financial feasibility analysis to see whether the business is feasible or not feasible. The data used were primary data and secondary data. Data were analyzed using Net Present Value (NPV), Gross Rate of Return (IRR) and Break Event Point (BEP). Based on the results of research conducted, the shallots breeding business was feasible because it had an NPV of Rp. 6,604,950,996.21 or more than 0, IRR 115.80% or higher than bank interest rates (6%) and Gross Benefit Cost Ratio 3.19 or more 1. Based on the results of the BEP analysis it was found that the break even point would be reached at the total production of 10,704 kg if the price of shallot seeds was Rp. 30,000/ kilogram.Keywords: Financial Analysis, Seed Breeding, Shallots, Southern Tonsewer